2011
DOI: 10.1007/s12032-011-9841-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced survival of patients with hepatocellular carcinoma expressing hexokinase II

Abstract: Hexokinase II is a key enzyme in the glycolytic pathway and possesses anti-apoptotic properties in tumor cells. The present study aimed to analyze the expression of hexokinase II and its clinical correlation with clinical factors in patients with hepatocellular carcinoma who treated surgically in China. Reverse transcription-polymerase chain reaction and real-time quantitative polymerase chain reaction were performed to determine hexokinase II mRNA expression in cancer tissues. Protein expression of hexokinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 31 publications
2
38
1
Order By: Relevance
“…The specimens were stained simultaneously under the same conditions, reducing the possibility that inter-batch differences in staining technique impacted the results. In contrast to previous works that reported HKII expression in only 45–56 % of samples [24, 25], the current study identified HKII expression in all 45 HCC specimens with an average value of 64.42 (±34.89) ppc/mm 2 . The differences between the results cannot be explained by variation in antibody or IHC methodology.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The specimens were stained simultaneously under the same conditions, reducing the possibility that inter-batch differences in staining technique impacted the results. In contrast to previous works that reported HKII expression in only 45–56 % of samples [24, 25], the current study identified HKII expression in all 45 HCC specimens with an average value of 64.42 (±34.89) ppc/mm 2 . The differences between the results cannot be explained by variation in antibody or IHC methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with recent publications, we noted HKII immunoexpression was more pronounced in poorly differentiated, pleomorphic, and in higher stage HCC [23–25], thereby adding to the evidence that HKII is a likely marker for increased metabolic activity that occurs in HCC in humans. The potential use of HK II inhibitors for the treatment of advanced HCCs was described in a mouse tumor model [43], and the question remains whether HKII provides an attractive target for the development of new agents for the treatment of HCC in humans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Silibinin dosedependently suppressed the expression of cortactin, CXCR4, GLI2, ID1, KIAA0101, mortalin, PAK1, RHOA, SPINK1, STAT3, and STMN1 in both cell types. The overexpression of these genes have been associated with cellular invasion and some serious life-threatening clinical features in HCC such as advanced histological grades, metastasis, and/or poor prognosis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In another aspect, ANGPT2 (overexpressed in HCC) and ID1 (in coordination with MMP-2) may induce angiogenesis in HCC, a hypervascular tumor (20,30).…”
Section: Discussionmentioning
confidence: 99%
“…While this may seem to be a wasteful form of energy production for highly proliferative cells since glycolysis nets only 2 ATP while the process of oxygen-dependent energy generation nets 36 ATP molecules, the upregulation of glucose transporters (e.g., GLUT-1) that allows for an increase in glucose uptake, combined with an increase in enzymes that contribute to glycolysis such as phosphoglycerate kinase-1 (PGK-1), hexokinase (HK), and phosphofructokinase L (PFK-L) [55,56], may allow the glycolytic flux to be high enough for the ATP production to match the seemingly more efficient ETC and coupled OXPHOS [57]. This upregulation of glycolytic metabolism participants has been correlated to poor prognosis in a variety of cancer types [58][59][60][61].…”
Section: Glucose Metabolismmentioning
confidence: 99%